The Importance of Integrating Local Culture Values in Science Learning by Supply Chain Strategy - A.A. Ketut Budiastra; Sardjijo Sardjijo (International Journal of Supply Chain Management, 2020)
Abstract— This study aims to examine the effectiveness of the model of integrating local cultural values in science learning in elementary school based on the supply chain strategy. The design of this study includes four stages, namely: (1) preliminary study; (2) design of learning models; (3) developing of learning models; and (4) validating the models in the science learning process in supply chain. In this study, step (3) and step (4) are carried out, while steps (1) and steps (2) have been implemented in the previous year. This research was carried out in several elementary schools: (1) in Dendang Belitung Timur District, Bangka Belitung; and (2) in Kediri Tabanan District, Bali. A total of 21 elementary school teachers and more than 300 elementary school students were included in this study. The results of this study, it can be seen that there is an increase in the ability of elementary school teachers to design and implement science learning by integrating local cultural values in science learning in the classroom. From the results of statistical tests, it is seen that there is an increase in student learning outcomes before and after the learning process takes place. In addition, most students appear to be actively participating and look happy during the learning process because the science content they learn is associated with local cultural values in their surroundings. The learning process like this makes it fun not only for elementary school teachers who teach but also makes students are happy in learning science.